Wanderings with Lady M.: A happy threesome - Adelheid L. J. Thieme (Mathematical Biosciences and Engineering)
I met Horst at the University of Münster, Germany, in July 1972. While I was at the university, one of my goals was to find a husband. I wanted my husband to be Catholic, so I decided to join a bible study group, where I thought I would find many suitable “candidates.” Unfortunately though, I was wrong. There were only two Catholics. One of them was definitely not an option, and then there was … Horst. He was a challenge, and I guess all participants of this conference know what I mean. But some people just grow on you, which happened in Horst’s case.   As our relationship was getting more serious, he said to me one day: “I need to tell you something. I am already engaged, and no matter what is going to happen between the two of us, I’m not going to give up my fiancée. If you manage to get along well with her, the three of us can have a good life together. I would like you to give the three of us a chance.”For more information please click the “Full Text” above.